Les logiques de la peur : le fantasme de l’invasion en Argentine durant le XXe siècle - Martin Pablo Otheguy (Les Cahiers ALHIM)
It is in the context of profound transformations of the era of classical Peronism that "the figure of the invasion" arises. The arrival of hundreds of thousands of internal immigrants in the public spaces of the capital produced a real social upheaval. The discriminatory epithet of cabecita negra forged by anti-Peronism shows the conflictuality that the acculturation of these migrants assumed with the illustrated middle classe and the elites of the capital. But the "fantasy of the invasion" is not confined to the emergence of this political movement. This work attempts to demonstrate that this recurrent collective fear in the country's history responds to the social logics underlying the edification, structuring and role of ethnic diversity in the nation's "invention". The study of phenomena related to ethnicity in Argentina leads to an interest in their relations, on the one hand, with the construction of the nation-state and, on the other hand, with the internal and external migration processes; nation, ethnicity and immigration constitute a major axis that organizes the social practices and representations of the country. It is indeed this generative principle that emerged in the course of the twentieth century a collective fear that structures the social space of Argentina.